Bisthiazolidines: A Substrate-Mimicking Scaffold as an Inhibitor of the NDM-1 Carbapenemase - Gonzalez, Mariano Martin (2016)
Pathogenic Gram-negative bacteria resistant to almost all β-lactam antibiotics are a major public health threat. Zn(II)-dependent or metallo-β-lactamases (MBLs) produced by these bacteria inactivate most β-lactam antibiotics, including the carbapenems, which are "last line therapies" for life-threatening Gram-negative infections. NDM-1 is a carbapenemase belonging to the MBL family that is rapidly spreading worldwide. Regrettably, inhibitors of MBLs are not yet developed. Here we present the bisthiazolidine (BTZ) scaffold as a structure with some features of β-lactam substrates, which can be modified with metal-binding groups to target the MBL active site. Inspired by known interactions of MBLs with β-lactams, we designed four BTZs that behave as in vitro NDM-1 inhibitors with Ki values in the low micromolar range (from 7 ± 1 to 19 ± 3 μM). NMR spectroscopy demonstrated that they inhibit hydrolysis of imipenem in NDM-1-producing Escherichia coli. In vitro time kill cell-based assays against a variety of bacterial strains harboring blaNDM-1 including Acinetobacter baumannii show that the compounds restore the antibacterial activity of imipenem. A crystal structure of the most potent heterocycle (L-CS319) in complex with NDM-1 at 1.9 Å resolution identified both structural determinants for inhibitor binding and opportunities for further improvements in potency.